(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Heavy training and less than optimal nutrient intake can cause physical stress on the body of football athletes, increasing the risk of injury and health problems. The nutritional content of red watermelon and red dragon fruit such as electrolytes, citrulline, and antioxidants are believed to have an ergogenic effect in helping to increase muscle endurance, and recovery processes and prevent oxidative stress in athletes. The purpose of this study was to analyze the effect of a combination of red watermelon and red dragon fruit on VO2max, leukocyte count, and pulse recovery of football athletes. This study used a quasi-experimental method with a non-randomized design and a control group pretest-posttest. The study population was 20 football athletes of Tadulako State Sports High School with the type of intervention in the form of giving segam juice for 14 days. The VO2max data collection technique used the beep test method, the leukocyte count used a hematology analyzer and the recovery pulse rate used a digital tensiometer with three measurement times, namely the 1st minute, the 3rd minute, and the 5th minute. Data analysis using a difference test with the help of SPSS. The results showed that there was a significant difference in VO2max values ​​between groups with an increase experienced by the SG group subjects (p-value=0.002). The number of leukocytes in both groups decreased after the intervention was carried out, but there was no significant difference between groups (p-value= 0.878). The SG group experienced a consistent decrease in pulse rate at all three measurement times with significant differences between groups at 1st minute (p-value=0.017) and 5th minute (p-value=0.007). Segam juice has an effect on increasing VO2max values ​​and pulse recovery of football athletes but does not affect the number of leukocytes after maximum physical activity.